The Role of Extrinsic Motivation and Quality Culture in Enhancing Higher Education Institutional Performance - Reni Farwitawati; Masirun Masirun; Souvya Fithrie (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to examine the effect of extrinsic motivation on higher education institutional performance, the effect of extrinsic motivation on quality culture, the effect of quality culture on higher education performance, and the mediating role of quality culture in the relationship between extrinsic motivation and institutional performance. A quantitative survey approach was employed involving 398 lecturers from higher education institutions in Riau Province, Indonesia, selected using the Slovin formula. Data were collected through an online questionnaire and analyzed using Partial Least Squares (PLS) with SmartPLS software. The results indicate that extrinsic motivation has a positive and significant effect on both higher education performance and quality culture. In addition, quality culture positively and significantly influences higher education performance. The mediation analysis confirms that quality culture mediates the relationship between extrinsic motivation and higher education performance, thereby strengthening the effect of extrinsic motivation on institutional performance through the enhancement of quality culture. These findings suggest that improving higher education performance depends not only on the provision of incentives and rewards but also on the institution’s ability to establish a sustainable quality culture.